Evaluation of the state-of-the-art in informatics in glucometers - Ajai, Oluseun; Tiwari, Ashutosh; Alcock, Jeffrey R. (Taylor & Francis, 2009)
This review evaluated the level of informatics in glucometers through an assessment of the quantity and types of information and advice provided to users. Manufacturer websites were investigated and the characteristics of glucometers were examined. One hundred glucometers from 27 manufacturers were analysed. Many glucometers contained simple informatics features and five also contained on-device graphing features for users to monitor trends. Some manufacturers have extended informatics via external software. A small number of glucometers provided knowledge for the user by, for example, simple embedded decision support protocols. However, it is suggested that glucometers could better serve as primary care devices through the incorporation of more decision support directly on the device.